Chitosan dressing: a clinical trial - Ahmad Alwi, Akmal Azim (IIUM Press, International Islamic University Malaysia, 2017)
The main objective of this clinical study was to compare the efficacy of chitosan sponge against an already commercialised Allevyn foam dressing on exudative wounds in terms of healing or epithelization. Other objectives include comparison of wound bed preparation, patients’ experience, practicality of the dressing and determination of any adverse reaction to the dressing. The research hypothesis was that there are significant differences in efficacy and healing properties between chitosan sponge and Allevyn as dressings for exudative wounds. A total of 72 subjects from 3 different hospitals were randomized into the study between July 2012 and August 2014 (24 months). Sixty (83.4%) completed the study and were equally divided into the chitosan and Allevyn groups. Twelve (16.6%) were discontinued, mainly due to non-compliant with the study protocol. The subjects were assessed clinically and their symptoms recorded every 3 days throughout the treatment duration. Data such as size of granulation and necrotic tissues, level of exudates, adherence, ease and pain on removal, odour, itchiness, were measured and recorded. Percentages of epithelization were measured by 2 blinded investigators via a series of photos taken at the start, middle and end of the treatments. The results showed that chitosan sponge had a higher mean percentage of epithelization than Allevyn but the difference was not statistically significant (p = 0.072). The rate of granulation tissue formation and reduction of necrotic tissue were also comparable between the 2 groups. No significant difference was found between the groups in terms of patients’ experience and performance of the dressings, apart from wound odour on Day 24, where chitosan was significantly worse (p = 0.02). There was no allergic or serious adverse reaction associated with chitosan sponge. In conclusion, there is no significant difference in efficacy and healing properties between chitosan sponge and Allevyn as dressings for exudative wounds. Hence, chitosan sponge has the potential to become as good an exudative wound dressing as the commercialised Allevyn.